2020
DOI: 10.3390/children7040028
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Points Change in the Association of Blood Pressure Subtypes with Anthropometric Indices of Adiposity among Children in a Rural Population

Abstract: Background: Hypertension has gained global significance and risk of cardiovascular disease, and adiposity is the most important of the conditions associated with and considered responsible for hypertension in children. Therefore, the present study aimed to determine whether indices of adiposity independently predicted blood pressure at multiple points in gender-specific groups. Methods: This was a cross-sectional study involving 10 randomly selected primary schools within the Ellisras Longitudinal Study, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our result showed adolescent with an increase of one BMI kg/m 2 was 1.12 times at risk of developing hypertension, that is, increase in one BMI kg/m 2 contributed by 12% of developing blood pressure among adolescents. Similar to our study, other studies have shown a positive association between adolescent hypertension and increasing BMI 10 14 24 28 29. In South Africa, a study included 1665 schoolchildren and adolescents (846 boys and 819 girls) aged 5 to 15 years showed an increase of one BMI kg/m 2 was associated with 1.198 times and 1.23 times risk of developing systolic and diastolic hypertension, respectively 24…”
Section: Discussionsupporting
confidence: 89%
“…Our result showed adolescent with an increase of one BMI kg/m 2 was 1.12 times at risk of developing hypertension, that is, increase in one BMI kg/m 2 contributed by 12% of developing blood pressure among adolescents. Similar to our study, other studies have shown a positive association between adolescent hypertension and increasing BMI 10 14 24 28 29. In South Africa, a study included 1665 schoolchildren and adolescents (846 boys and 819 girls) aged 5 to 15 years showed an increase of one BMI kg/m 2 was associated with 1.198 times and 1.23 times risk of developing systolic and diastolic hypertension, respectively 24…”
Section: Discussionsupporting
confidence: 89%
“…Of 60 articles identified from the title and abstract screening, 53 presented data on hypertension prevalence specifically for African children between 1-19 years age range. Reasons for the exclusion of the remaining 7 articles were: Blood pressure (BP) was self-reported and not measured (n=1) (Letamo et al) [26] , the study sample spanned outside the desirable age range in which no age specific data could be extracted (n=2) (Bhimma et al [27] , Mokgwathi et al [28] ), the study was not conducted within an African population residing in Africa (n=2) (South et al [29] , South et al [30] ) and no extractable information regarding hypertension could be extracted from the results (n=2) (Muyumba et al [31] , Mphekgwana et al [32] ) ( Figure 1 ).
Figure 1 Flow diagram of the study selection.
…”
Section: Resultsmentioning
confidence: 99%
“…Of 60 articles identified from the title and abstract screening, 53 presented data on hypertension prevalence specifically for African children between 1-19 years age range. Reasons for the exclusion of the remaining 7 articles were: Blood pressure (BP) was selfreported and not measured (n=1) (Letamo et al) [26], the study sample spanned outside the desirable age range in which no age specific data could be extracted (n=2) (Bhimma et al [27], Mokgwathi et al [28]), the study was not conducted within an African population residing in Africa (n=2) (South et al [29], South et al [30]) and no extractable information regarding hypertension could be extracted from the results (n=2) (Muyumba et al [31], Mphekgwana et al [32]) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%